Caenorhabditis elegans cell biology and physiology - Rothman, Joel H.; Singson, Andrew (Waltham, MA Academic Press is an imprint of Elsevier, 2012)
The second part of an updated edition of the classic Methods in Cell Biology, Volume 48, this book emphasizes diverse methods and technologies needed to investigate C. elegans, both as an integrated organism and as a model system for research inquiries in cell, developmental, and molecular biology, as well as in genetics and pharmacology. By directing its audience to tried-and-true and cutting-edge recipes for research, this comprehensive collection is intended to guide investigators of C. elegans for years to come.--Provided by publisher.
Pt.I Imaging instrumentation : High-resolution imaging of cellular processes in caenorhabditis elegans / Amy S. Maddox, Paul S. Maddox -- Immunofluorescence microscopy / Diane C. Shakes, David M. Miller III, Michael L. Nonet -- Fluorescent protein methods : strategies and applications / Harald Hutter -- Modern electron microscopy methods for C. elegans / David H. Hall, Erika Hartwieg, Ken C.Q. Nguyen -- Pt.II Cell biology : Culture and manipulation of embryonic cells / Lois G. Edgar, Bob Goldstein -- Laser microsurgery in caenorhabditis elgans / Christopher Fang-Yen, Christopher V. Gabel, Aravinthan D.T. Samuel, Cornelia I. Bargmann, Leon Avery -- Methods in cell biology : analysis of cell polarity in C. elegans embryos / Olaf Bossinger, Carrie R. Cowan -- Analysis of membrane-bound organelles / Hanna Fares, Alexander M. van der Bliek -- C. elegans cell cycle analysis / Sander van den Heuvel, Edward T. Kipreos -- Pt.III Physiology : Methods for studying programmed cell death in C. elegans / Yi-Chun Wu, Xiaochen Wang, Ding Xue -- Methods for studying the DNA damage response in the caenorhabdatis elegans germ line / Ashley L. Craig, Sandra C. Moser, Aymeric P. Bailly, Anton Gartner -- Analysis of aging in caenorhabditis elegans / Deepti S. Wilkinson, Rebecca C. Taylor, Andrew Dillin -- Analyses of C. elegans fat metabolic pathways / Alexandre Guimarães de Almeida Barros, Jason Liu, George A. Lemieux, Brendna C. Mullaney, Kaveh Ashrafi -- Electrophysiological methods for caenorhabditis elegans neurobiology / Miriam B. Goodman, Theodore H. Lindsay, Shawn R. Lockery, Janet E. Richmond
Includes bibliographical references and index.
Keywords: Caenorhabditis elegans; Electronic books